Effect of Zinc Supplementation in the Diet on Sikumbang Janti Female Duck Performance, Carcass, Digestive Organs, and Intestinal Morphology - Ridho Kurniawan Rusli; Robi Amizar; Zurmiati Zurmiati; Ananda Ananda; Arif Darmawan; Kusnadidi Subekti; Khalil Khalil (Jurnal Ilmu Ternak dan Veteriner, 2023)
The research aimed to evaluate the effect of Zn supplementation in diet of Sikumbang Janti female duck on its performance, carcass, digestive organs, and intestinal morphology. The study used 96 female ducks aged 8 weeks. This research used a completely randomized design with four treatments (0, 30, 60, and 90 mg Zn/kg), each treatment was repeated four times. Performance, carcass, digestive organs, and intestinal morphology were observed. The results showed that Zn supplementation significantly (P0.05) affected body weight, body weight gain, feed conversion ratio, carcass weight, abdominal fat, and intestinal morphology, but it did not affect (P0.05) feed consumption, carcass percentage, and digestive organs. In conclusion, supplementation of 60 mg Zn/kg in the diet improved performance, intestinal morphology, and the health of visceral of Sikumbang Janti female ducks aged 8 to 16 weeks.